West's Federal Taxation: Comprehensive Volume, 1986 Annual Edition/West's Federal Taxation: Individual Income Taxes, 1986 Annual Edition (Book). - Hendrickson, Harvey S.; Dillaway, Manson P. (The Accounting Review, 1986)
Reviews two books. "West's Federal Taxation: Comprehensive Volume, 1986 Annual Edition," edited by William H. Hoffman and Eugene Willis; "West's Federal Taxation: Individual Income Taxes, 1986 Annual Edition," edited by William H. Hoffman and Eugene Willis.